The apparent focal depth, emergence angle, and take-off angle of seismic wave measured by YRY-4-type borehole strainmeter as one kind of strain seismograph - Tang, Lei; Qiu, Zehua; Fan, Junyi; Yin, Zhigang (Frontiers in Earth Science, 2023)
Introduction: In theory, the observation objects and principles of strain seismograph and traditional pendulum seismograph are different, and the characteristics of observed signals should also be dissimilar. The observation results of pendulum seismograph show that seismic waves in inhomogeneous media will undergo refraction, reflection, and attenuation. Then, what signal characteristics can be detected by strain seismograph is great significance for understanding and explaining the observation results. Methods: Using YRY-4 type four-gauge borehole strainmeter as one kind of strain seismograph to detect the strain tensor change of the plane seismic wave emitted from the surface, a five-site strain seismograph observation network was built in Shanxi Province, with continuous observation for 2 years at a sampling rate of 100 Hz. In this paper, two local events occurring in the area covered by the strain seismograph observation network are taken as examples. We systematically studied the characteristics of seismic wave signals recorded by strain seismographs at five sites, inverted for the focal depth of the two local earthquakes and the relationship between the wave velocity and the wave velocity gradient of the focal depth, and calculated the apparent focal depth, the emergence angle and the take-off angle of seismic waves. Results: These results show stable uniqueness and apparent regularity, especially since the inverted focal depths are basically consistent with the seismic solutions based on those traditional pendulum seismographs. The observations from this study show that the strain seismograph can be used as an effective supplement to the pendulum seismograph. Discussion: In the future, we will continue to study the rupture process and focal mechanism of moderate-strong earthquakes and teleseismic earthquakes by combining two kinds of observations.